Compositional and Structural Evolution during Ball Milling of Ti-based Metallic Glass Powder - Yanuar Rohmat (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
Ti42Zr40Ta3Si7.5Sn7.5metallic glass powder prepared for subsequent consolidation by hot pressing were produced by high energy ball milling from amorphous ribbon and both of the compositional and structural evolution on milled powders were studied using XRD and DSC analyses. By using WC vial and balls, the abrasion of milling media occurred causing WC contamination on < 105 µm milled powder after 2 cycles of milling. Based on DSC analysis, the contamination clearly reduced theΔTxof the alloy up to 48%. On the other hand, the contamination were overcome after milling using SS vial and balls, proved by no crystal peak observed on XRD pattern of all milling cycle levels. However, the thermal stability was noticed to be decreased implying the presence of nanocrystals on the amorphous powder after ball milling and the nanocrystal amount tend to be higher when more milling cycles were applied.